Fair shared green and recreational spaces guidelines for gender-responsive and inclusive design Tbilisi Municipality
This publication aims to inform the sustainable development of Tbilisi to give residents a better quality of life while protecting their heritage and preserving the green landscape. The guidelines identify priorities for improvements and for ensuring that limited resources are targeted at the areas of most need. They were developed jointly by the Asian Development Bank and the Municipal Department of Environmental Protection of Tbilisi City Hall.